The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/1450102
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Alignment: A Review of Impact Studies in Entrepreneurship Education

Abstract: This study uses the concept of alignment as a framework to examine empirical research on the impact of entrepreneurship education interventions on students. Alignment assumes that effective instruction requires congruence between three instructional components: intended outcomes, instructional processes, and assessment criteria. Given the extant diversity and complexity of entrepreneurship education impact, scholars have not been able to explain how teaching approaches and methods are being adjusted to the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
(137 reference statements)
0
39
0
5
Order By: Relevance
“…It is also well implemented that learning with peers' interaction will transfer the feelings of experiments into a real context (Hamari, 2013;Ryan & Deci, 2000). Furthermore, most studies of entrepreneurship training are unable to develop longitudinal approach and direct relationship between training and entrepreneurship behaviors (Fayolle et al, 2016;Kamovich & Foss, 2017). This study, therefore, focuses on the development of entrepreneurial intention as part of entrepreneurship behavior (Carr & Sequeira, 2007;Kautonen et al, 2009;Kautonen et al, 2015;Schwarz Erich, 2009).…”
Section: Entrepreneurshipmentioning
confidence: 99%
“…It is also well implemented that learning with peers' interaction will transfer the feelings of experiments into a real context (Hamari, 2013;Ryan & Deci, 2000). Furthermore, most studies of entrepreneurship training are unable to develop longitudinal approach and direct relationship between training and entrepreneurship behaviors (Fayolle et al, 2016;Kamovich & Foss, 2017). This study, therefore, focuses on the development of entrepreneurial intention as part of entrepreneurship behavior (Carr & Sequeira, 2007;Kautonen et al, 2009;Kautonen et al, 2015;Schwarz Erich, 2009).…”
Section: Entrepreneurshipmentioning
confidence: 99%
“…Overall, practitioners, policy makers and also scientists seem to be convinced about the positive impact of EE; EE seems to be beneficial for the development of all sorts of early stage entrepreneurial outcomes, for instance entrepreneurial intentions, skills and attitudes (Bae, Qian, Miao, & Fiet, ; Martin, McNally, & Kay, ). However, meta‐analyses and systematic reviews also highlight methodological weaknesses (e.g., lack of control groups) in EE studies and, from an educational sciences point of view, lack of detailed reporting on alignment between teaching/learning objectives, delivery mode and impact assessment mode (Kamovich & Foss, ). Moreover, Kamovich and Foss () clearly conclude in their systematic review that research on the impact of EE has raced ahead of the theory necessary to confirm and explain it.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, meta‐analyses and systematic reviews also highlight methodological weaknesses (e.g., lack of control groups) in EE studies and, from an educational sciences point of view, lack of detailed reporting on alignment between teaching/learning objectives, delivery mode and impact assessment mode (Kamovich & Foss, ). Moreover, Kamovich and Foss () clearly conclude in their systematic review that research on the impact of EE has raced ahead of the theory necessary to confirm and explain it. One area—which informs EE on a practical as well as theoretical level—in which much progress has been made during the last 5 to 10 years is that of the development of competence frameworks.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…RESEARCH CONTEXT: MEASURING THE IMPACT OF EE Impact studies on EE aim to establish whether a pedagogical intervention has caused any change in specific outcome variables. The outcomes measured need to be carefully aligned with the intended learning outcomes for the EE course (Kamovich and Foss, 2017) and may address changes in students' hearts, minds and behaviour (Souitaris et al, 2007). The importance of evaluating the outcomes of EE has been widely acknowledged (Mets et al, 2017), and different frameworks have been suggested for categorizing entrepreneurship learning outcomes.…”
Section: Introductionmentioning
confidence: 99%